Arenga pinnata Merr. Reinforced Polyester Biocomposite as a Candidate Material for Fishing Vessel Hull: Mechanical Properties Analysis - Pakaya, Fahriadi; Nantan, Yurika; Ch. Huwae, Jozua; S. Tappy , Marinus; GTH Simanjuntak, Raman; Wasum; Subawa, I Nyoman (Maritime Park: Journal of Maritime Technology and Society, 2025)
Arenga pinnata Merr (APM) has excellent strength compared to other natural fibers. However, until now its application in the industrial sector is still very low. This study is an experimental study aimed at analyzing the mechanical properties of Arenga pinnata Merr “ijuk” reinforced polyester biocomposite and its potential as a basic material for fiber ship hulls with alkalization treatment on the fiber. This research method is based on mechanical testing of several specimens with fiber content of 0, 5, 10, 15, to 20%wt soaked in 2% NaOH solvent for 3 hours, temperature 70oC. Furthermore, tensile testing of single fiber and biocomposite, bending test, hardness test, and Impact test were carried out with 5 repetitions each. The results obtained include a single fiber tensile strength of 1.1 GPa. For the highest composite tensile strength at 15%wt fiber of 61.27 MPa. The highest Elongation value at 20%wt fiber (3.19%). The highest bending strength at 0%wt fiber is 93.21 MPa. The highest hardness value at 5%wt fiber is 83.7 HD and the impact toughness value on the composite with 20%wt fiber is 1.31 J/mm2. Based on the results of the biocomposite mechanical test, if the biocomposite material is used as the basic material for making fiber ship hulls, then based on BKI standards, the mechanical strength value of the polyester-APM biocomposite does not comply with BKI standards.